The Brand Image Perception of Indirect Comparative Advertisements: Lipton Ice Tea “Don’t Choose the Easy Way” Ad Case - Mehmet Sinan Tam; İpek Krom (İletişim Kuram ve Araştırma Dergisi)
Comparative advertising is to make comparisons between two brands by making indirect or direct explicit references to the product of a certain brand. Comparative advertising is used to reveal the advantages, differences and qualities of a certain product or brand in a way that will attract the attention of the consumer. The impact of comparative advertisements on brand image has been discussed by advertising agency managers and in academic researches for many years. For this purpose, a sample of 18 participants, 9 males and 9 females, aged 22-59, from different professional groups was selected for the study using purposive sampling. In the research where the content analysis method was used, the brand image perception of indirect comparative ads was examined through Lipton Ice Tea's 'Drink Lipton, Don't Choose the Easy Way' advertising case. According to the findings, the participants above middle age have a more positive attitude towards comparative ads and the purchasing intention of the female participants, especially mothers, increased after watching the ad.